2009
DOI: 10.1152/jn.90844.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Electrocorticogram Signal Can Be Modulated With Deep Brain Stimulation of the Subthalamic Nucleus in the Hemiparkinsonian Rat

Abstract: Electrocorticogram (ECoG) recordings of the 6-hydroxydopamine (6-OHDA)-lesioned parkinsonian rat have shown an increase in the power of cortical beta-band (15-30 Hz) oscillations ipsilateral to the lesion. The power of these oscillations is decreased with dopamine agonist administration. Here, we demonstrate that stimulation of an electrode implanted in the subthalamic nucleus alters the power of cortical beta and gamma oscillations in 6-OHDA-lesioned animals. These alterations are dependent on stimulation fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
8
21
0
Order By: Relevance
“…2) could result from changes in the substantia nigra input that reduce the collicular response to trigeminal input from the condition stimulus. Our demonstration that 16-Hz STN DBS creates R2 trigeminal reflex blink hyperexcitability in normal rats (Kaminer et al 2014) supports the hypothesis that hypersynchronized beta oscillations associated with PD (Brown and Eusebio 2008;Gatev et al 2006;Jenkinson and Brown 2011) and the 6-OHDA rat model (Lehmkuhle et al 2009;Li et al 2007;Mallet et al 2008;McConnell et al 2012;Sharott et al 2005) can reduce the responsiveness of collicular neurons to trigeminal inputs in PD. The suppression of beta oscillations by 130-Hz STN DBS (Dorval et al 2010;McConnell et al 2012;Ray et al 2008;Wingeier et al 2006) and its restoration of normal blink reflex excitability (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…2) could result from changes in the substantia nigra input that reduce the collicular response to trigeminal input from the condition stimulus. Our demonstration that 16-Hz STN DBS creates R2 trigeminal reflex blink hyperexcitability in normal rats (Kaminer et al 2014) supports the hypothesis that hypersynchronized beta oscillations associated with PD (Brown and Eusebio 2008;Gatev et al 2006;Jenkinson and Brown 2011) and the 6-OHDA rat model (Lehmkuhle et al 2009;Li et al 2007;Mallet et al 2008;McConnell et al 2012;Sharott et al 2005) can reduce the responsiveness of collicular neurons to trigeminal inputs in PD. The suppression of beta oscillations by 130-Hz STN DBS (Dorval et al 2010;McConnell et al 2012;Ray et al 2008;Wingeier et al 2006) and its restoration of normal blink reflex excitability (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…3 and 4). Given the apparent importance of hypersynchronized beta oscillations in impairing blink plasticity (Kaminer et al 2014), 130-Hz STN DBS may restore plasticity by suppressing exaggerated beta oscillations in 6-OHDA lesioned rats (Lehmkuhle et al 2009;Li et al 2007;McConnell et al 2012). Our experiment showing that delivering 130-Hz STN DBS only during the HFS-B treatment (130-D) restores blink reflex plasticity (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Much evidence has suggested the presence of exaggerated oscillations in the cortical-basal ganglion circuit at beta frequencies (oscillations around 20Hz). Exaggerated beta oscillations closely parallel the key PD motor deficits, bradykinesia, rigidty, akinesia, and tremor (Levy, Hutchison et al 2000;Brown, Oliviero et al 2001;Levy, Hutchison et al 2002;Boraud, Brown et al 2005;, and are largely suppressed by effective dopamine replacement treatment (Brown, Oliviero et al 2001;Levy, Ashby et al 2002;Williams, Tijssen et al 2002;Priori, Foffani et al 2004;Silberstein, Pogosyan et al 2005) and DBS (Wingeier, Tcheng et al 2006;Kuhn, Kempf et al 2008;Kuhn, Tsui et al 2009;Lehmkuhle, Bhangoo et al 2009). It has thus been suggested that DBS therapeutic effect is through reducing beta oscillations.…”
Section: Therapeutic Mechanisms Of Dbs For Pdmentioning
confidence: 95%